Programming interviews exposed : coding your way through the interview - Mongan, John (Wrox professional guides, 2018)
"Programming interviews exposed" is the programmer's ideal first choice for technical interview preparation. Updated to reflect changing techniques and trends, this new fourth edition provides insider guidance on the unique interview process that today's programmers face. Online coding contests are being used to screen candidate pools of thousands, and employers are even evaluating a candidate's public code repositories at GitHub, and with competition becoming increasingly fierce, programmers need to shape themselves into the ideal candidate well in advance of the interview. "Programming interviews exposed" will help you: Learn what the interviewer needs to hear to move you forward in the process ; Adopt an effective approach to phone screens with nontechnical recruiters ; Examine common interview problems and tests with expert explanations ; Be ready to demonstrate your skills verbally, in contests, on GitHub, and more ; Demonstrate your skillset under pressure ; Stand out as the best candidate for the job.